Do Governance Mechanisms Fail? Evidence From Indonesia’s Technology Sector - Arief Darmawan; Ali Rahman Reza Zaputra; Marlina Marlina (Journal of Accounting Science, 2026)
General Background: Fraudulent Financial Reporting undermines financial reliability and investor confidence. Corporate governance and internal audit are key mechanisms to reduce fraud risk. Specific Background: In the technology sector, rapid growth, uncertainty, and performance pressure—especially during the “tech winter”—increase incentives for earnings manipulation, raising doubts about governance effectiveness. Knowledge Gap: The effectiveness of governance and internal audit remains unclear due to inconsistent findings and reliance on disclosure-based measures. Research on Indonesia’s technology sector is still limited. Objective: This study examines the relationship between Good Corporate Governance, internal audit effectiveness, and fraudulent financial reporting in Indonesian technology companies during the 2022–2024 period. Method : Using 93 firm-year observations from 31 listed firms by employs disclosure-based indices to measure governance and internal audit effectiveness while the Beneish M-Score is used to identify the likelihood of financial statement manipulation. Multiple regression analysis is applied to evaluate the relationship between the variables. Results : The findings reveal that neither corporate governance nor internal audit effectiveness has a significant effect on fraudulent financial reporting. Furthermore, the model demonstrates relatively low explanatory power, suggesting that financial reporting fraud may be influenced more strongly by other organizational or financial factors. These results also indicate that governance practices within the sector may tend to emphasize formal compliance rather than substantive monitoring effectiveness. Novelty : This study challenges agency theory assumptions and highlights the limitations of disclosure-based proxies in capturing actual governance effectiveness. Implications: Formal compliance alone is insufficient to prevent fraudulent financial reporting. Companies should improve the quality of governance implementation and regulators should adopt quality-based supervision approaches and investors are encouraged to complement governance assessments with forensic financial analysis.